2017
DOI: 10.1080/00913847.2018.1409604
|View full text |Cite
|
Sign up to set email alerts
|

Acute lateral ankle sprain to chronic ankle instability: a pathway of dysfunction

Abstract: Lateral ankle sprains (LAS) have been reported as one of the most common musculoskeletal injuries observed in sports and in individuals who are recreationally active. Approximately 40% of individuals who sustain a LAS develop a condition known as chronic ankle instability (CAI). Years of research has identified numerous impairments associated with CAI such as decreases in range of motion (ROM), strength, postural control, and altered movement patterns during functional activities when compared to individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 56 publications
1
84
0
13
Order By: Relevance
“…Labbe et al [ 39 ] demonstrated that tDCS targeting the right S1 improved vibrotactile detection and the discrimination threshold of the middle finger in healthy younger adults compared to sham. The diminished proprioception in CAI could lead to the overall sensory dysfunction of the ankle joint [ 40 ], which could cause dysfunction of muscles and nerves. This functional impairment may be more affected by the cerebral cortex [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Labbe et al [ 39 ] demonstrated that tDCS targeting the right S1 improved vibrotactile detection and the discrimination threshold of the middle finger in healthy younger adults compared to sham. The diminished proprioception in CAI could lead to the overall sensory dysfunction of the ankle joint [ 40 ], which could cause dysfunction of muscles and nerves. This functional impairment may be more affected by the cerebral cortex [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, 30% of patients have been reported to be injured again because patients tend to exercise or exercise before recovery. 28 According to previous research, overuse of painkillers 29 and steroid injections 30 is not recommended. Therefore, the fact that the proportion of Western prescriptions and injections decreased over the 3 years is considered positive.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CAI, Miklovic et al (2018) identi ed four impairments domains (range of motion, strength, proprioception, functional tasks) that were likely not adequately treated after the primary LAS. Consequently, the authors recommend considering these functional de cits already at an early stage during rehabilitation after an acute LAS to prevent persistent or even chronic symptoms (13).…”
Section: Introductionmentioning
confidence: 99%